Doing what makes sense: locating knowledge about person-centred care in the everyday logics of long-term care - Scales, Kezia (2014)
Addressing criticisms of the routine-driven, task-oriented, depersonalising nature of conventional services, and reflecting a broader trend across health and social care, person-centred care has become the watchword for quality in long-term care for older people in recent years. Person-centred care requires recognising the unique personhood of each individual regardless of their physical or mental capacity. Efforts to realise this approach depend largely on the non-professional nursing staff who deliver the majority of direct care in this context. However, little is known about how new knowledge, including ideas and evidence about person-centred care, translates into the daily practices of this cadre of staff, who have little formal training, low job status, and limited access to traditional forms of research dissemination and knowledge exchange.